The quest for assay robustness across the life cycle of a bioanalytical method. (April 2015) - White, Stephen; Dunn, John; Summerfield, Scott
White has been an analytical chemist for 28 years, with a range of knowledge and experience across multiple disciplines including pharmaceuticals, foodstuffs, environmental and forensic analysis. Steve works within the regulated bioanalytical group at GSK supporting both preclinical and clinical bioanalysis. His responsibilities have included leadership of bioanalytical, dose formulation and sample management teams as well as assisting with the set up of the Anti-Doping Testing Laboratory for the London 2012 Olympics. In his current role, Steve is part of the UK bioanalytical leadership team with a focus on regulatory & compliance issues. Steve is the small molecule rep for GSK within the European Bioanalysis Forum (EBF), a member of the EBF Steering Committee and also contributed to the Global Bioanalysis Consortium S2 team. The successful validation or qualification of an assay plus incurred sample reproducibility gives the bioanalyst confidence of assay suitability. However, these elements alone do not give the full picture of how reliable an assay may be during routine production use for analysis of unknown study samples. The robustness of an assay can be understood by applying key performance indicators to monitor assay performance pre- and post-transfer between laboratories, plus a cross-validation step during assay transfer. The measurement of assay robustness (beyond the context of cross-validation) should not be considered as yet another regulatory layer, but more as a means for the bioanalyst to better understand an individual assay within a large portfolio, when used for its intended purpose.